Corporate governance: Golden parachute for minority shareholders / Ng Boon Siong - Ng , Boon Siong (2012)

(untitled)
As rightly put by Sealy (1996), the law has to strike a delicate balance in cases of tussles between the majority and minority shareholders. Although the legal and regulatory apparatus in Malaysia have shown great alacrity in the recent years endeavouring to rewrite the corporate rules and revamp its legal landscape, it remains nigh impossible to legally define a thin crystal clear demarcation line between the protection afforded to the minority shareholders and the consideration of the corporate interest as a whole. Such thorny situations may arise when the court is faced with the dilemma of giving overwhelmed support to the majority at the expense of prejudicing the minority where the court is prepared to condone unfair acts and decisions of the majority. Conversely, the day-today operation of the company may be hindered if the court tends to favour the exasperating demands and objections of the dissatisfying minorities. This predicament inevitably devolves an onerous task of striking a balance upon the court in leaving the internal management to the company whilst ensuring that the interest of the minorities is not imperilled. Hence, it is high time for the best practices of corporate governance to step in and act as the golden scale to complement the imperfection of law in balancing the rights of the majority and the minority shareholders with the holistic view of enhancing shareholder values. As an alternative remedy, the protective measure of corporate governance may well hold the answer to the din of corporate malpractices. This study has an international magnitude but with a focus on Malaysian public-listed corporations which involve the public investors at large. The methodology of this study aims at providing positive descriptive analysis of the corporate governance best practices for the purpose of minority shareholders’ activism and protection. The methodology adopted was mainly premised on a qualitative approach via massive literature review and identification of governance mechanisms that focus on the best practices of corporate governance. This study delved into the issues of corporate governance based on content analysis with specific reference to case studies and reports in order to derive a set of best practices of corporate governance for the protection of the minority shareholders. The findings of this research will have significant implications for improving the overall corporate governance practices in Malaysia in that they highlight the protection of the minority shareholders in the corporate governance regime. Unlike most studies on corporate governance issues in Malaysia and East Asian countries which are based on strong quantitative methodological focus and being scattered in numerous disciplines, this research aims to provide a more in-depth legal insights and understanding of corporate governance practices, using qualitative and analytical study based approach. Ultimately, the golden parachute of corporate governance best practices will land the minority shareholders on gold mine of corporate prosperity in order to achieve a higher standard of Malaysian corporate governance. The main objective of this dissertation lies in the formulation of corporate governance best practices for the protection of the minority shareholders.